Micro/nano composites: a simple and safe way to fabricate nanomaterials. (2nd May 2007) - Pecharroman, C.; Esteban-Cubillo, A.; Torrecillas, R.; Moya, J.S.
In this paper we detail how the use of nanoparticles supported or embedded in microparticles (nanostructured powders) may overcome many of the problems of nanoparticle manipulation as well as allowing bulk compacts in which nanoparticles appear monodisperse to be obtained. The main advantage of this procedure is that the possibility to use the well developed knowledge about compounding of microparticles to obtain dense composites instead of developing new methods to handling nanoparticles. The obtained nanostructured powders or dense composites can be used for different applications, such as medical implants, cutting tools, optical devices, magnetic powders, etc. Examples of alumina/nano-zirconia, alumina/nano-YAG, zirconia/nano-nickel, alumina/nano-Ag and sepiolite/nano-(Cu, Au, Ag, Ni and Fe) are also reported.